An Investigation of Electromagnetic Field Effect On a Human Skin Cell Using Numerical Method Approaches - Ismail, Mohd Muzafar; zainudin, Muhamamd Noorazlan; Meor said, Maizatul Alice; Abd Rahim, Rosman (IEEE Malaysia Chapter, 2011)
Abstract—the investigation between electromagnetic waves (conduction current) and human cell as lossless material has received renewed attention recently. This propagation can come from many sources such as cellular phone. The structure of a human cell were studied from many school of thinking such as biochemical in cell, cytoplasm, nucleus and membrane and the understanding obtained have been used as the basis in the developing of mathematical model. The main objective of this project is to analyze the behavior and determine the parameters of the interaction and propagation in a single cell when expose to electromagnetic wave from lossy material to lossless material such as the attenuation coefficient, electric field and skin depth. The Maxwell equations were used as the basis of the modeling in this project with aid of numerical method approaches specifically Finite-Difference Time Domain (FDTD) techniques and applications. To develop the model MATLAB tool and Graphical Users Interface (GUI) were used. Results obtained from the developed model ware verified with known result obtained from others researchers and with experimentally.